Case report: The stroma-rich variant of Castleman’s disease of hyaline-vascular type with atypical stromal cell proliferation and malignant potential: An exceptional rare case occurred in mediastinal lymph node - Shi, Xiaoxin; Liao, Mengying; Yin, Xiaomin; Chen, Yaoli; Huang, Chuqiang; Yin, Weihua; Li, Jian (Frontiers in Oncology, 2023)
The stroma-rich variant of Castleman disease of hyaline-vascular type (SR-HVCD) is characterized by interfollicular proliferation of the fibroblastic, myofibroblastic, and/or histiocytic-derived stromal cells, occurred in a background of Castleman disease of hyaline-vascular type (HVCD). It has been considered as a hyperplastic disorder by far. Herein, we presented a case of a 40-year-old male suffering from an occupation in the right middle mediastinum. Microscopically, the lesion was characterized by atretic lymphoid follicles and overgrowth of the interfollicular spindle-shaped cells. Those spindle cells were histologically bland in some areas, while exhibited notable cellular atypia and focal necrosis in other areas. SMA and CD68 were immunostained with a subset of the spindle cells in both areas, whereas p53 staining was only perceived in areas with markedly cellular atypia. In addition, indolent T-lymphoblastic proliferation (iT-LBP) was present inside the lesion. The patient developed multiple sites metastases 4 months after surgery, and succumbed to the disease at 7 months. Our case demonstrates for the first time that SR-HVCD have a tumorigenesis potential rather than a simple hyperplastic process. Such disorder should be carefully evaluated to avoid underdiagnosis.